2001
DOI: 10.1523/jneurosci.21-03-00798.2001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Plasticity in Tachykinin and Tachykinin Receptor Expression after Focal Cerebral Ischemia Is Differentially Linked to GABAergic and Glutamatergic Cerebrocortical Circuits and Cerebrovenular Endothelium

Abstract: To test the hypothesis of an involvement of tachykinins in destabilization and hyperexcitation of neuronal circuits, gliosis, and neuroinflammation during cerebral ischemia, we investigated cell-specific expressional changes of the genes encoding substance P (SP), neurokinin B (NKB), and the tachykinin/ neurokinin receptors (NK1, NK2, and NK3) after middle cerebral artery occlusion (MCAO) in the rat. Our analysis by quantitative in situ hybridization, immunohistochemistry, and confocal microscopy was concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 74 publications
2
96
0
Order By: Relevance
“…The contribution of tachykinins in excitotoxic neurotransmission has been proposed for various pathological conditions in the nervous system, including nociception in spinal cord (Saria 1999), epilepsy in hippocampus (Liu et al 1999) and cerebral ischemia in cortex (Stumm et al 2001). Most recent studies demonstrated the co-localization of neuronal nitric oxide synthase (nNOS) and NK-1 receptor in striatal interneurons (Li et al 2001), as well as the direct projections from SP-containing neurons to nNOS-containing interneurons in the striatum (Li et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of tachykinins in excitotoxic neurotransmission has been proposed for various pathological conditions in the nervous system, including nociception in spinal cord (Saria 1999), epilepsy in hippocampus (Liu et al 1999) and cerebral ischemia in cortex (Stumm et al 2001). Most recent studies demonstrated the co-localization of neuronal nitric oxide synthase (nNOS) and NK-1 receptor in striatal interneurons (Li et al 2001), as well as the direct projections from SP-containing neurons to nNOS-containing interneurons in the striatum (Li et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The coding sequences of M6a, M6b (GI: 9502118), and DM20 were amplified by PCR and then subcloned into the pGEM-T easy vector (Promega) for producing relative riboprobes. Generation of 35 S-labeled and digoxigeninlabeled riboprobes, hybridization, washing procedures, and detection of hybridization signals were performed as described (20). Hybridization signal densities of the sense probes were defined as background levels.…”
Section: Methodsmentioning
confidence: 99%
“…Permanent MCAO and sham operation were performed in 6-week-old male Long-Evans rats (Mollegaard) as described previously (Culmsee et al, 1999;Stumm et al, 2001), with the modification that sodium pentobarbital was applied (40 mg/kg, i.p.) for anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Densitometric analysis of hybridization signals and cell counts were conducted as described previously (Stumm et al, 2001) using NIH Image 1.62. For densitometry, sections of an experimental group, the respective control group, and a […”
Section: Methodsmentioning
confidence: 99%